Implementasi Watermarking Pada Gambar Menggunakan Matlab Untuk Mencegah Plagiarisme Laporan Praktikum - Gimnastiar, Alfin; Harahap, Lailan Sofinah; Abdillah, Rizky (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
The ease of digital data exchange, especially images, has increased the risk of plagiarism in academic environments, particularly in student laboratory reports. To address this issue, this study implements a text watermarking technique directly on digital images using the insertText() function in MATLAB. This method falls under the category of visible watermarking, where identity information—such as the student’s name—is embedded in the image to be visually recognizable. The process involves several stages, including reading the image, defining the watermark text, configuring the position and visual appearance, and saving the final result. Experimental results show that the watermark can be effectively embedded without disrupting the main content of the image and remains readable even after basic manipulations such as rotation, resizing, or format conversion. This method is considered simple, efficient, and suitable for academic purposes, promoting academic integrity and preventing plagiarism among students.